Non-Pharmacological Pain Management In Patient With Gouty Arthritis: A Narrative Review - Novia Yulianti; Nursiswati Nursiswati; Siti Ulfah Rifa'atul Fitri (Jurnal Berita Ilmu Keperawatan, 2023)
Gouty arthritis is a condition characterized by joint inflammation due to the accumulation of monosodium urate crystals in the joint, resulting in severe pain, reduced musculoskeletal ability, and poor QoL. Therefore, this study aims to identify non-pharmacological pain management in gouty arthritis sufferers. This study is a narrative review including three databases such as ScienceDirect, Proquest, Pubmed, and the search engine Google Scholar. It was conducted using keywords such as gouty arthritis, non-pharmacology, and pain management. The article was sorted by cyclical criteria, and assessment was performed using JBI Critical Appraisal tools. The results showed that non-pharmacological interventions such as warm compresses using moringa leaves, lemongrass decoction water, ginger, cinnamon, soursop leaves, and CQBG (compound Qingbi granules) are effective in reducing gouty arthritis pain and have no side effects. Therefore, this study is expected to provide useful information and insights regarding pain management to health workers, nurses, sufferers, and the general public.